Energy Challenges and Opportunities for Future Data-Driven Operations in the United States Air Force: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On April 27-29, 2020, the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on U.S. Air Force (USAF) data-driven operations’ energy challenges as part of a broader study focused on this topic. Subject experts from government, industry, and academia discussed steps and plans the USAF is taking and/or should be considering now to successfully develop, deploy, and sustain the weapons systems needed to compete in an emerging information-rich environment. This publication summarizes the presentations and discussions from the workshop.
Keywords: Conflict and Security Issues; Energy and Energy Conservation

Future Directions for the U.S. Geological Survey's Energy Resources Program - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Reliable, affordable, and technically recoverable energy is central to the nation's economic and social vitality. The United States is both a major consumer of geologically based energy resources from around the world and - increasingly of late - a developer of its own energy resources. Understanding the national and global availability of those resources as well as the environmental impacts of their development is essential for strategic decision making related to the nation's energy mix. The U.S. Geological Survey Energy Resources Program is charged with providing unbiased and publicly available national- and regional-scale assessments of the location, quantity, and quality of geologically based energy resources and with undertaking research related to their development. At the request of the Energy Resources Program (ERP), this publication considers the nation's geologically based energy resource challenges in the context of current national and international energy outlooks. Future Directions for the U.S. Geological Survey's Energy Resources Program examines how ERP activities and products address those challenges and align with the needs federal and nonfederal consumers of ERP products. This study contains recommendations to develop ERP products over the next 10-15 years that will most effectively inform both USGS energy research priorities and the energy needs and priorities of the U.S. government.
Keywords: Energy and Energy Conservation

Energy Reduction at U.S. Air Force Facilities Using Industrial Processes: A Workshop Summary - National Research Council (The National Academies Press, 2013)
The Department of Defense (DoD) is the largest consumer of energy in the federal government. In turn, the U.S. Air Force is the largest consumer of energy in the DoD, with a total annual energy expenditure of around $10 billion. Approximately 84 percent of Air Force energy use involves liquid fuel consumed in aviation whereas approximately 12 percent is energy (primarily electricity) used in facilities on the ground. This workshop was concerned primarily with opportunities to reduce energy consumption within Air Force facilities that employ energy intensive industrial processes—for example, assembly/disassembly, painting, metal working, and operation of radar facilities—such as those that occur in the maintenance depots and testing facilities. Air Force efforts to reduce energy consumption are driven largely by external goals and mandates derived from Congressional legislation and executive orders. To date, these goals and mandates have targeted the energy used at the building or facility level rather than in specific industrial processes.
Keywords: Energy and Energy Conservation; Conflict and Security Issues

Energy Futures and Urban Air Pollution: Challenges for China and the United States - National Academy of Engineering; National Research Council (The National Academies Press, 2008)
The United States and China are the top two energy consumers in the world. As a consequence, they are also the top two emitters of numerous air pollutants which have local, regional, and global impacts. Urbanization has led to serious air pollution problems in U.S. and Chinese cities; although U.S. cities continues to face challenges, the lessons they have learned in managing energy use and air quality are relevant to the Chinese experience. This report summarizes current trends, profiles two U.S. and two Chinese cities, and recommends key actions to enable each country to continue to improve urban air quality.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Urbanization, Energy, and Air Pollution in China: The Challenges Ahead: Proceedings of a Symposium - National Research Council; National Academy of Engineering (The National Academies Press, 2004)
In October 2003, a group of experts met in Beijing under the auspices of the Chinese Academy of Sciences, Chinese Academy of Engineering, and National Academy of Engineering (NAE)/National Research Council (NRC) of the National Academies to continue a dialogue and eventually chart a rational course of energy use in China. This collection of papers is intended to introduce the reader to the complicated problems of urban air pollution and energy choices in China.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Decreasing Energy Intensity in Manufacturing: Assessing the Strategies and Future Directions of the Industrial Technologies Program - National Research Council (The National Academies Press, 2005)
The U.S. Department of Energy (DOE) has supported the Industrial Technologies Program (ITP) for more than a decade. This program supports R&D into energy efficiency technologies designed to decrease the energy intensity of the U.S. industrial sector. The focus in on seven energy-intensive industries—aluminum, chemicals, forest products, glass, metal casting, mining, and steel—known as the Industries of the Future (IOF). DOE asked the NRC for a review of this program including an evaluation of the ITP strategic plan, an evaluation of the technical quality of individual subprogram plans, and the prospective value of the multi-year program plan. This report presents the results of that review. It contains an assessment of the ITP strategy, of how effective it is being implemented, and the likelihood of achieving program goals. It also provides conclusions about the quality of the subprograms and recommendations about how to strengthen the subprograms and the overall program.
Keywords: Engineering and Technology; Energy and Energy Conservation; Industry and Labor

Advanced Exploratory Research Directions for Extraction and Processing of Oil and Gas (The National Academies Press, 1993)
Keywords: Energy and Energy Conservation

Methodology for Estimating Prospective Benefits of Energy R&D Programs - National Research Council (The National Academies Press, 2004)
Since its inception in 1977, the Department of Energy has invested substantial sums in energy efficiency and fossil energy R&D. To monitor its effectiveness, the agency and Congress have, over the years, pursued evaluation of these R&D programs that focuses on its cost and benefits. Such evaluation, however, is difficult and must incorporate the full range of public benefits as well as what might happen if that R&D had not been funded by the federal government. To help address these challenges, and at the direction of Congress, DOE asked the NRC to develop a methodology for evaluating the prospective benefits of its fossil energy and energy efficiency R&D programs. Such methodology can be used to evaluate program management and funding decisions on an ongoing basis. This letter report provides an overview of the studies approach and how it differs from retrospective studies of this R&D previously carried out by the NRC.

New Methods of Heating Buildings (The National Academies Press, 1960)
Keywords: Energy and Energy Conservation

Research and Information Needs for Management of Oil Shale Development (The National Academies Press, 1983)
Keywords: Energy and Energy Conservation

Evaluation of Coal-Gasification Technology: Part II, Low- and Intermediate-BTU Fuel Gases (The National Academies Press, 1973)
Keywords: Energy and Energy Conservation

Energy Storage for Solar Applications (The National Academies Press, 1981)
Keywords: Energy and Energy Conservation

Energy for Rural Development: Renewable Resources and Alternative Technologies for Developing Countries: Supplement (The National Academies Press, 1981)
Keywords: Energy and Energy Conservation

A Review of the 1984 Department of Energy Health and Environment Effects Documents on Coal Liquefaction and Oil Shale Technologies (The National Academies Press, 1985)
Keywords: Energy and Energy Conservation

Energy Research at DOE: Was It Worth It? Energy Efficiency and Fossil Energy Research 1978 to 2000 - National Research Council (The National Academies Press, 2001)
In legislation appropriating funds for DOE's fiscal year (FY) 2000 energy R&D budget, the House Interior Appropriations Subcommittee directed an evaluation of the benefits that have accrued to the nation from the R&D conducted since 1978 in DOE's energy efficiency and fossil energy programs. In response to the congressional charge, the National Research Council formed the Committee on Benefits of DOE R&D on Energy Efficiency and Fossil Energy. From its inception, DOE's energy R&D program has been the subject of many outside evaluations. The present evaluation asks whether the benefits of the program have justified the considerable expenditure of public funds since DOE's formation in 1977, and, unlike earlier evaluations, it takes a comprehensive look at the actual outcomes of DOE's research over two decades.
Keywords: Energy and Energy Conservation

Advanced Technologies for Gas Turbines - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Leadership in gas turbine technologies is of continuing importance as the value of gas turbine production is projected to grow substantially by 2030 and beyond. Power generation, aviation, and the oil and gas industries rely on advanced technologies for gas turbines. Market trends including world demographics, energy security and resilience, decarbonization, and customer profiles are rapidly changing and influencing the future of these industries and gas turbine technologies. Technology trends that define the technological environment in which gas turbine research and development will take place are also changing - including inexpensive, large scale computational capabilities, highly autonomous systems, additive manufacturing, and cybersecurity. It is important to evaluate how these changes influence the gas turbine industry and how to manage these changes moving forward. Advanced Technologies for Gas Turbines identifies high-priority opportunities for improving and creating advanced technologies that can be introduced into the design and manufacture of gas turbines to enhance their performance. The goals of this report are to assess the 2030 gas turbine global landscape via analysis of global leadership, market trends, and technology trends that impact gas turbine applications, develop a prioritization process, define high-priority research goals, identify high-priority research areas and topics to achieve the specified goals, and direct future research. Findings and recommendations from this report are important in guiding research within the gas turbine industry and advancing electrical power generation, commercial and military aviation, and oil and gas production.
Keywords: Energy and Energy Conservation

The Hydrogen Economy: Opportunities, Costs, Barriers, and R&D Needs - National Research Council; National Academy of Engineering (The National Academies Press, 2004)
The announcement of a hydrogen fuel initiative in the President’s 2003 State of the Union speech substantially increased interest in the potential for hydrogen to play a major role in the nation’s long-term energy future. Prior to that event, DOE asked the National Research Council to examine key technical issues about the hydrogen economy to assist in the development of its hydrogen R&D program. Included in the assessment were the current state of technology; future cost estimates; CO2 emissions; distribution, storage, and end use considerations; and the DOE RD&D program. The report provides an assessment of hydrogen as a fuel in the nation’s future energy economy and describes a number of important challenges that must be overcome if it is to make a major energy contribution. Topics covered include the hydrogen end-use technologies, transportation, hydrogen production technologies, and transition issues for hydrogen in vehicles.
Keywords: Energy and Energy Conservation

Hidden Costs of Energy: Unpriced Consequences of Energy Production and Use - National Research Council (The National Academies Press, 2010)
Despite the many benefits of energy, most of which are reflected in energy market prices, the production, distribution, and use of energy causes negative effects. Many of these negative effects are not reflected in energy market prices. When market failures like this occur, there may be a case for government interventions in the form of regulations, taxes, fees, tradable permits, or other instruments that will motivate recognition of these external or hidden costs. The Hidden Costs of Energy defines and evaluates key external costs and benefits that are associated with the production, distribution, and use of energy, but are not reflected in market prices. The damage estimates presented are substantial and reflect damages from air pollution associated with electricity generation, motor vehicle transportation, and heat generation. The book also considers other effects not quantified in dollar amounts, such as damages from climate change, effects of some air pollutants such as mercury, and risks to national security. While not a comprehensive guide to policy, this analysis indicates that major initiatives to further reduce other emissions, improve energy efficiency, or shift to a cleaner electricity generating mix could substantially reduce the damages of external effects. A first step in minimizing the adverse consequences of new energy technologies is to better understand these external effects and damages. The Hidden Costs of Energy will therefore be a vital informational tool for government policy makers, scientists, and economists in even the earliest stages of research and development on energy technologies.
Keywords: Energy and Energy Conservation

Environmental Impacts of Wind-Energy Projects - National Research Council (The National Academies Press, 2007)
The generation of electricity by wind energy has the potential to reduce environmental impacts caused by the use of fossil fuels. Although the use of wind energy to generate electricity is increasing rapidly in the United States, government guidance to help communities and developers evaluate and plan proposed wind-energy projects is lacking. Environmental Impacts of Wind-Energy Projects offers an analysis of the environmental benefits and drawbacks of wind energy, along with an evaluation guide to aid decision-making about projects. It includes a case study of the mid-Atlantic highlands, a mountainous area that spans parts of West Virginia, Virginia, Maryland, and Pennsylvania. This book will inform policy makers at the federal, state, and local levels.
Keywords: Energy and Energy Conservation

Prospective Evaluation of Applied Energy Research and Development at DOE (Phase One): A First Look Forward - National Research Council (The National Academies Press, 2005)
In 2001, the National Research Council (NRC) completed a congressionally mandated assessment of the benefits and costs of DOE's fossil energy and energy efficiency R&D programs, Energy Research at DOE: Was It Worth It? The Congress followed this retrospective study by directing DOE to request the NRC to develop a methodology for assessing prospective benefits. The first phase of this project—development of the methodology—began in December 2003. Phase two will make the methodology more robust and explore related issues, and subsequent phases will apply the methodology to review the prospective benefits of different DOE fossil energy and energy efficiency R&D programs. In developing this project, three considerations were particularly important. First, the study should adapt the work of the retrospective study. Second, the project should develop a methodology that provides a rigorous calculation of benefits and risks, and a practical and consistent process for its application. Third, the methodology should be transparent, should not require extensive resources for implementation, and should produce easily understood results. This report presents the results of phase one. It focuses on adaptation of the retrospective methodology to a prospective context.
Keywords: Energy and Energy Conservation